1998
DOI: 10.1597/1545-1569(1998)035<0454:bofswc>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Branchio-Oculo-Facial Syndrome with Cleft Lip and Bilateral Dermal Thymus

Abstract: The BOF syndrome must be considered as a neurocristopathy at different levels, with a tiny mesencephalo-prosencephalic lesion and a severe rhombencephalic lesion that includes seven consecutive hindbrain segments, from rhombomere 2 to rhombomere 8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Two patients had heterochromic irides [Patient 14; Stoetzel et al, 2009, Patient 1.2]. Congenital heart defects were rare (∼8% among total patients), including two atrial septal defects [Patient 24; Gestri et al, 2009 Patient 2], and one tetralogy of Fallot [Reiber et al, 2010a, Patient SP2, previously reported by Bennaceur et al, 1998]. Two probands in our series had bilateral post‐axial polydactyly that was not present in their families.…”
Section: Resultsmentioning
confidence: 59%
“…Two patients had heterochromic irides [Patient 14; Stoetzel et al, 2009, Patient 1.2]. Congenital heart defects were rare (∼8% among total patients), including two atrial septal defects [Patient 24; Gestri et al, 2009 Patient 2], and one tetralogy of Fallot [Reiber et al, 2010a, Patient SP2, previously reported by Bennaceur et al, 1998]. Two probands in our series had bilateral post‐axial polydactyly that was not present in their families.…”
Section: Resultsmentioning
confidence: 59%
“…In medical databases such as OMIM 1 and LMD (London Medical Database) 6 , there is no description of the association between BOFS and congenital heart defects. However, in our review, we found four confirmed cases of BOFS presenting CHD which included: ostium secundum atrial septal defect (two cases) 3,7 , tetralogy of Fallot (one case) 5 and pulmonary valve stenosis (one case) 8 (Table 1). All patients presented facial findings characteristic of BOFS associated with branchial defects 1,3,5,8 .…”
Section: Discussionmentioning
confidence: 92%
“…However, in our review, we found four confirmed cases of BOFS presenting CHD which included: ostium secundum atrial septal defect (two cases) 3,7 , tetralogy of Fallot (one case) 5 and pulmonary valve stenosis (one case) 8 (Table 1). All patients presented facial findings characteristic of BOFS associated with branchial defects 1,3,5,8 . The present report is the first description of a patient with both BOFS and AVSD, one of the CHD more frequently associated with extracardiac anomalies, especially with Down syndrome 9 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations